Inflammatory Breast Cancer and Warm Antibody Autoimmune Hemolytic Anemia: A Rare Paraneoplastic Syndrome. (November 2017) - Ugoeke, Nene; Onweni, Chidinma; Treece, Jennifer; Pai, Vandana; Arikapudi, Sowminya; Kulbacki, Evan; Bajaj, Kailash
Autoimmune hemolytic anemia (AIHA) is a disease process that involves the destruction of red blood cells mediated by the humoral immune system. It can be characterized as a cold agglutinin syndrome, paroxysmal cold hemoglobinuria, and warm, mixed type, and drug-induced AIHA. Although a well-established relationship exists between the presence of AIHA and lymphoproliferative malignancy, AIHA rarely presents in association with solid malignancies. An analysis of the limited number of published cases of AIHA in association with solid malignancies performed showed that AIHA may present before the diagnosis of a solid malignancy, concurrently with the presence of a solid malignancy, or even on resolution of a solid malignancy. Few cases of solid cancers associated with AIHA have been reported. AIHA rarely presents as a paraneoplastic syndrome indicating existence of a solid cancer. We report a case of inflammatory breast cancer with AIHA.